2017
DOI: 10.1111/apha.12930
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of muscle fibre conduction velocity for representative samples of motor units in the full recruitment range of the tibialis anterior muscle

Abstract: were decomposed into single motor unit action potentials, from which the corresponding motor unit RT, 32 MUCV, and action potential amplitude were estimated. Established relations between muscle fiber diameter 33 and CV were used to estimate the fiber size. 34Results: Within individual subjects, the distributions of MUCV and fiber diameters were unimodal and did 35 not show distinct populations. MUCV was strongly correlated with RT (mean (SD) R 2 = 0.7 (0.09), p<0.001; 36 406 motor units), which supported the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
83
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(102 citation statements)
references
References 49 publications
16
83
0
3
Order By: Relevance
“…; Del Vecchio et al . , ). The motor unit action potentials with high correlation values (>0.7) were visually inspected.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…; Del Vecchio et al . , ). The motor unit action potentials with high correlation values (>0.7) were visually inspected.…”
Section: Methodsmentioning
confidence: 99%
“…It has recently been shown that the activity of large populations of motor units can be identified (Holobar & Zazula, 2007;Muceli et al 2015;Farina et al 2016;Negro et al 2016;Del Vecchio et al 2018c) and tracked over multiple sessions (Martinez-Valdes et al 2017) during relatively strong voluntary contractions (70% of maximum, Holobar et al 2014;Del Vecchio et al 2017, 2018b. Once the reliability of the tracking procedure had been confirmed, the present study aimed to quantify the change in discharge characteristics of the same motor units in tibialis anterior after a 4 week strength training intervention with the dorsiflexor muscles.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Manuscripts from 2018 indicate how much attention very young manuscripts are receiving . Listed here are less than half of the original articles receiving double‐digit citations.…”
mentioning
confidence: 99%